MALDI mass spectrometry imaging of N‐glycans on tibial cartilage and subchondral bone proteins in knee osteoarthritis. Issue 11 (15th June 2016) - Briggs, Matthew T.; Kuliwaba, Julia S.; Muratovic, Dzenita; Everest‐Dass, Arun V.; Packer, Nicolle H.; Findlay, David M.; Hoffmann, Peter
Abstract : Magnetic resonance imaging (MRI) is a non‐invasive technique routinely used to investigate pathological changes in knee osteoarthritis (OA) patients. MRI uniquely reveals zones of the most severe change in the subchondral bone (SCB) in OA, called bone marrow lesions (BMLs). BMLs have diagnostic and prognostic significance in OA, but MRI does not provide a molecular understanding of BMLs. Multiple N ‐glycan structures have been observed to play a pivotal role in the OA disease process. We applied matrix‐assisted laser desorption/ionization (MALDI) mass spectrometry imaging (MSI) of N ‐glycans to formalin‐fixed paraffin‐embedded (FFPE) SCB tissue sections from patients with knee OA, and liquid chromatography‐electrospray ionization‐tandem mass spectrometry (LC‐ESI‐MS/MS) was conducted on consecutive sections to structurally characterize and correlate with the N ‐glycans seen by MALDI‐MSI. The application of this novel MALDI‐MSI protocol has enabled the first steps to spatially investigate the N ‐glycome in the SCB of knee OA patients.